Tinjauan Hukum Islam terhadap Pembayaran Zakat Profesi dengan Sistem Payroll (Studi Kasus pada PT. PLN Persero, Unit Induk Wilayah Sulselbar) - Herman, Sulkifli; bin Anshor, Saifullah; Akhmad Hanafi Dain Yunta; Siti Munawira S (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Zakat on the profession is a new term that has never been conveyed by previous scholars. This concept of zakat was invented by a contemporary scholar, namely YÅ«suf al-Qará¸ÄwÄ« in his book of zakat. The purpose of this study was to determine the view of Islamic law on the payment of zakat of a profession with the payroll system and the payment mechanism of zakat of a profession with the payroll system at PT. PLN (Persero) Regional Main Unit SULSELBAR. The method used in this research was a qualitative method with a normative juridical approach. The results showed that the professional zakat expenditure mechanism with the payroll system at PT. PLN (Persero) Regional Unit SULSELBAR has not met the criteria for zakat of profession that must be paid since it is not required to reach the nisab and does not pass a year (haul), although, with this payroll system, zakat payment becomes more regular, easy, and effective.